2020
DOI: 10.1111/cpf.12665
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional echocardiography to identify right ventricular dilatation in patients with corrected Fallot anomaly or pulmonary stenosis

Abstract: Background 3‐Dimensional Echocardiography allows measuring volumes and parameters of myocardial deformation (strain). Myocardial strain has been suggested to be superior to conventional echo parameters in the assessment of right ventricular (RV) function. Myocardial strain can be assessed by cardiac magnetic resonance (CMR) or two‐ and three‐dimensional echocardiography (2D and 3DEcho). We performed a comprehensive assessment of the RV based on 3DEcho and compared the results with those based on CMR and 2DEcho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The correlation coefficients are almost above 0.7 for RV volumes (RVEDV and RVESV). The 3DE underestimates the RV volumes [13,16,19,28,[36][37][38][39]41,43,46,48,49,52,56], except in the case of Muraro, D. et al study for which RVESV was overestimated [19]. The mean differences were as followed: −2.3 to −53 mL for RVEDV and −0.3 to −23.6 mL for RVESV.…”
Section: Reliability Feasibility and Reproducibility Of Rv Volumes An...mentioning
confidence: 87%
See 1 more Smart Citation
“…The correlation coefficients are almost above 0.7 for RV volumes (RVEDV and RVESV). The 3DE underestimates the RV volumes [13,16,19,28,[36][37][38][39]41,43,46,48,49,52,56], except in the case of Muraro, D. et al study for which RVESV was overestimated [19]. The mean differences were as followed: −2.3 to −53 mL for RVEDV and −0.3 to −23.6 mL for RVESV.…”
Section: Reliability Feasibility and Reproducibility Of Rv Volumes An...mentioning
confidence: 87%
“…The correlation coefficients of 3DE-derived RVEF with CMR values in most of the studies exceed 0.75, and the mean difference for RVEF between 3DE and CMR is discordant. Some studies showed that 3DE slightly underestimates the RVEF against CMR [16,28,36,39,41,43,46,49,56]. The mean bias for RVEF ranged from −0.3% to −17.0%.…”
Section: Reliability Feasibility and Reproducibility Of Rv Volumes An...mentioning
confidence: 99%
“…A study including corrected Fallot anomaly or pulmonary stenosis patients performed by Trzebiatowska-Krzynska et al . [ 16 ] demonstrated that 3DE successfully identified all patients with RV dilatation according to CMRI. In addition, the reproducibility analysis results showed that limits of agreement of 3D data, such as EDV, ESV and RVEF, were narrow in this research population.…”
Section: Discussionmentioning
confidence: 99%
“…As stated earlier, RV function is an independent predictor of clinical outcomes in patients with PAH. Most studies reported a lower estimation of RVEF by 3DE in comparison with CMR [22,26,29,30,32,47] except the study of Bhave et al, [44] where a slight overestimation was found in comparison with CMR. Similar trends were observed in the case of patients with PH who underwent 3DE.…”
Section: Reliability and Feasibility Of Rv Remodeling In Ph Assessed ...mentioning
confidence: 99%